POTENSI SENI KRIYA ISTIMEWA DALAM PAMERAN “NEGARI NGAYOGYAKARTA HADININGRAT 2012” - Edi Eskak (Institut Seni Indonesia Yogyakarta, 2012)
Arts Festival Negari Ngayogyakarta Hadiningrat 2012 undertaken in order to commemoratethe first century of Hamengku Buwono IX as well as 2,5 century of Ngayogyakarta Hadiningrat,featuring the character or the privilege of Yogyakarta through works of art by artists with no exitfrom the corridors of copyrighted artistic distinctiveness. The works on display most of the particularcharacter, specific and have their own specialty. Privileges of Yogyakarta with its dynamic,multicultural, and tolerant of the works reflected on display in the various mediums of expression andcreation.A wide assortment of works of art displayed expression of both the traditional, conventionaland non conventional, such as: painting, graphics, sculpture, video, film, animation, installation,performance art, digital prints, puppets, mixed media and others.Not to mention that the exhibition has a variety of craft works of art, such as the art which haselements of craftmanship. The uncommon art that relies on creativity ideas and handskills in thisexhibition appear surprisingly with exceptional works that have creative potential prospective. Theseyoung artists, among other craft; Karyadi, Fitriasih Pudyo Atmaningrum, I Gde Suryawan, and I GustiNgurah Edi Basudewa. Keywords: potential, arts crafts, specialty, and Negari Ngayogyakarta Hadiningrat